Effect of Preflaring on Accuracy of Endodontic Length Determination by Four Electronic Apex Locators - Izadi, Arash; Bayandari, Maliheh; Kazeminejad, Ezatolah (Journal of Dentistry Indonesia, 2022)
Objective: Root canal anatomy significantly impacts the working length determination. This study aimed to investigate the effect of the preflaring technique on the accuracy of four electronic apex locators. Methods: Forty-five single-canal central maxillary teeth were selected. The working length was measured before and after the coronal preparation by four types of electronic apex locators in the range of ±0.5 and ±1 mm matched for the apical constriction. The actual working length was calculated under a microscope. Data were analyzed using ICC and paired t-tests in SPSS16. A p < 0.05 was considered significant. Results: The accuracies of Root ZX, DTE, Denjoy, and Coxo apex locators in the range of ± 0.05 mm were 71.1, 93.3, 84.4, and 75.6% before preflaring, and 82.2, 93.3, 97.8, and 100% after that. The corresponding values in the range of ±1 mm were 86.7, 97.8, 93.3, and 100% before and 97.8, 100, 100, and 100% after preflaring. Significant differences were found between the working lengths measured by the four devices and the actual working lengths before and after preflaring. Conclusion: The preflaring technique could impact the performance of apex locators in determining the working length and may be advocated for better outcomes.